Question
upstudy study bank question image url

(g) \( x+2 y=0 \quad \) and \( y-x y=\frac{1}{2} x^{2}-2 \) (h) \( y=\frac{-6}{x+2}-1 \) and \( y+2 x-6=0 \) (i) \( y=\frac{3}{x}+3 \quad \) and \( 3 y-x=1 \)

Ask by Tucker Pope. in South Africa
Feb 26,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solutions are: - (g) \( (4, -2) \) - (h) \( (-2.5, 11) \) and \( (4, -2) \) - (i) \( (-1, 0) \) and \( (9, 3.\dot{3}) \)

Solution

Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}x+2y=0\\y-xy=\frac{1}{2}x^{2}-2\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=-2y\\y-xy=\frac{1}{2}x^{2}-2\end{array}\right.\) - step2: Substitute the value of \(x:\) \(y-\left(-2y\times y\right)=\frac{1}{2}\left(-2y\right)^{2}-2\) - step3: Simplify: \(y+2y^{2}=2y^{2}-2\) - step4: Cancel equal terms: \(y=-2\) - step5: Substitute the value of \(y:\) \(x=-2\left(-2\right)\) - step6: Calculate: \(x=4\) - step7: Calculate: \(\left\{ \begin{array}{l}x=4\\y=-2\end{array}\right.\) - step8: Check the solution: \(\left\{ \begin{array}{l}x=4\\y=-2\end{array}\right.\) - step9: Rewrite: \(\left(x,y\right) = \left(4,-2\right)\) Solve the system of equations \( y=\frac{3}{x}+3; 3y-x=1 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}y=\frac{3}{x}+3\\3y-x=1\end{array}\right.\) - step1: Substitute the value of \(y:\) \(3\left(\frac{3}{x}+3\right)-x=1\) - step2: Multiply the terms: \(\frac{9+9x}{x}-x=1\) - step3: Multiply both sides of the equation by LCD: \(\left(\frac{9+9x}{x}-x\right)x=1\times x\) - step4: Simplify the equation: \(9+9x-x^{2}=x\) - step5: Move the expression to the left side: \(9+9x-x^{2}-x=0\) - step6: Subtract the terms: \(9+8x-x^{2}=0\) - step7: Factor the expression: \(\left(9-x\right)\left(1+x\right)=0\) - step8: Separate into possible cases: \(\begin{align}&9-x=0\\&1+x=0\end{align}\) - step9: Solve the equation: \(\begin{align}&x=9\\&x=-1\end{align}\) - step10: Calculate: \(x=9\cup x=-1\) - step11: Rearrange the terms: \(\left\{ \begin{array}{l}x=9\\y=\frac{3}{x}+3\end{array}\right.\cup \left\{ \begin{array}{l}x=-1\\y=\frac{3}{x}+3\end{array}\right.\) - step12: Calculate: \(\left\{ \begin{array}{l}x=9\\y=\frac{10}{3}\end{array}\right.\cup \left\{ \begin{array}{l}x=-1\\y=0\end{array}\right.\) - step13: Calculate: \(\left\{ \begin{array}{l}x=-1\\y=0\end{array}\right.\cup \left\{ \begin{array}{l}x=9\\y=\frac{10}{3}\end{array}\right.\) - step14: Check the solution: \(\left\{ \begin{array}{l}x=-1\\y=0\end{array}\right.\cup \left\{ \begin{array}{l}x=9\\y=\frac{10}{3}\end{array}\right.\) - step15: Rewrite: \(\left(x,y\right) = \left(-1,0\right)\cup \left(x,y\right) = \left(9,\frac{10}{3}\right)\) Solve the system of equations \( y=\frac{-6}{x+2}-1; y+2x-6=0 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}y=\frac{-6}{x+2}-1\\y+2x-6=0\end{array}\right.\) - step1: Calculate: \(\left\{ \begin{array}{l}y=-\frac{6}{x+2}-1\\y+2x-6=0\end{array}\right.\) - step2: Substitute the value of \(y:\) \(-\frac{6}{x+2}-1+2x-6=0\) - step3: Simplify: \(-\frac{6}{x+2}-7+2x=0\) - step4: Multiply both sides of the equation by LCD: \(\left(-\frac{6}{x+2}-7+2x\right)\left(x+2\right)=0\times \left(x+2\right)\) - step5: Simplify the equation: \(-20-3x+2x^{2}=0\) - step6: Factor the expression: \(\left(-4+x\right)\left(5+2x\right)=0\) - step7: Separate into possible cases: \(\begin{align}&-4+x=0\\&5+2x=0\end{align}\) - step8: Solve the equation: \(\begin{align}&x=4\\&x=-\frac{5}{2}\end{align}\) - step9: Calculate: \(x=4\cup x=-\frac{5}{2}\) - step10: Rearrange the terms: \(\left\{ \begin{array}{l}x=4\\y=-\frac{6}{x+2}-1\end{array}\right.\cup \left\{ \begin{array}{l}x=-\frac{5}{2}\\y=-\frac{6}{x+2}-1\end{array}\right.\) - step11: Calculate: \(\left\{ \begin{array}{l}x=4\\y=-2\end{array}\right.\cup \left\{ \begin{array}{l}x=-\frac{5}{2}\\y=11\end{array}\right.\) - step12: Calculate: \(\left\{ \begin{array}{l}x=-\frac{5}{2}\\y=11\end{array}\right.\cup \left\{ \begin{array}{l}x=4\\y=-2\end{array}\right.\) - step13: Check the solution: \(\left\{ \begin{array}{l}x=-\frac{5}{2}\\y=11\end{array}\right.\cup \left\{ \begin{array}{l}x=4\\y=-2\end{array}\right.\) - step14: Rewrite: \(\left(x,y\right) = \left(-\frac{5}{2},11\right)\cup \left(x,y\right) = \left(4,-2\right)\) Here are the solutions for the given systems of equations: ### (g) Equations: 1. \( x + 2y = 0 \) 2. \( y - xy = \frac{1}{2}x^2 - 2 \) **Solution:** The solution to this system is: \[ (x, y) = (4, -2) \] ### (h) Equations: 1. \( y = \frac{-6}{x+2} - 1 \) 2. \( y + 2x - 6 = 0 \) **Solution:** The solutions to this system are: \[ (x, y) = \left(-\frac{5}{2}, 11\right) \cup (x, y) = (4, -2) \] This means there are two pairs of solutions: one at \((-2.5, 11)\) and another at \((4, -2)\). ### (i) Equations: 1. \( y = \frac{3}{x} + 3 \) 2. \( 3y - x = 1 \) **Solution:** The solutions to this system are: \[ (x, y) = (-1, 0) \cup (x, y) = (9, \frac{10}{3}) \] This means there are two pairs of solutions: one at \((-1, 0)\) and another at \((9, 3.\dot{3})\). If you have any further questions or need additional assistance, feel free to ask!

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution
Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy